Clear cell sarcoma-like tumour of the ileum. Issue 10 (October 2015) - Kalimuthu, Sangeetha N.; Chetty, Runjan
Abstract: Clear cell sarcoma-like tumour (CCSLT) of the gastrointestinal tract are rare malignant tumours and derive their name from their morphological resemblance to clear cell sarcoma (CSS) of soft tissue. We report a case of an 83-year old lady with a CCSLT in the ileum. Microscopically, the tumour was composed of uniform spindle to epithelioid cells, organized in nests. In addition, scattered intervening osteoclast-like giant cells were also noted. Melanin pigment deposition was not a feature. The tumour cells were positive for S100, SOX-10, CD56 and synaptophysin (focal) and negative for HMB45, Melan-A, MiTF, epithelial markers, desmin, caldesmon, smooth muscle actin (SMA), CD117, DOG1, CD34 and chromogranin. Fluorescence in situ hybridization (FISH) for EWSR1 displayed a split signal indicating a chromosomal translocation. This was further confirmed by RT-PCR analysis which demonstrated EWS/CREB1 translocation: t(2;22). The overall features confirmed a diagnosis of CCSLT of the gastrointestinal tract. Recognition of these tumours is important, particularly given the morphological resemblance to conventional CCS. As such, CCSLT should be suspected in spindled to epithelioid intramural tumours of the gastrointestinal tract with S100 positivity and showing no other specific melanocytic differentiation.